Kashmir Conflict and Environmental Issues: An Appraisal - Aqeela Asif; Syed Qandil Abbas; Muhammad Asif Javed; Sunbal Siddique, (ASIAN Journal of International Peace & Security (AJIPS), 2023)
The modern world entered the 21st century with multiple issues related to human societies in different parts of the globe, including rapid climate and environmental changes. Intergovernmental Panel on Climate Change (IPCC) issued cautions regarding global greenhouse gas emissions. Long standing political territorial issues like Kashmir are making the situation more complex due to recent climate and environmental changes in the South Asian region. The main objective of this paper is to highlight the political tension between Pakistan and India on Kashmir with the blend of environmental issues in the wake of massive climate changes in the region. The problem of environmental and climate changes in the presence of rigid political policies make the territorial dispute more complex and the consequences may become unexpectedly horrible. In this era, nontraditional security threats such as population data manipulation and inflicting damage to opponent countries through floods and other environmental changes can have dire consequences for the target states. This study is qualitative and analytical for which secondary data have been collected from diverse sources. Thematic analysis method has been used to evaluate the data, generate the patterns and draw conclusions.